2019
DOI: 10.3390/ani9020033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Barley and Lysine Supplementation of Pasture-Based Diet on Growth, Carcass Composition and Physical Quality Attributes of Meat from Farmed Fallow Deer (Dama dama)

Abstract: Fallow deer (Dama dama) are important meat producing species providing venison and other products to an international market. The present study investigated the effects of different feed rations on the growth, carcass characteristics and physical attributes of the longissimus lumborum (LL) and semitendinosus (SET) muscles of 45 farm-raised male fallow deer. The animals were divided into three separate groups: 15 pasture-fed (P), 15 pasture-fed and supplemented with barley (B), and 15 pasture-fed and supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…In general, deer species have a high lean meat:bone ratio (5.5:1 in FD and 5:1 in red deer) and a higher proportion of lean meat (from 66 to 83%) than more conventionally raised ruminant species (Kudrnáčová et al 2018 ). However, lower lean meat:bone ratio was noted (3.4:1) in this study although the results are in agreement with the findings of Kudrnáčová et al ( 2019 ), who reported a similar meat:bone ratio in 17-month old FD (3.42:1).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In general, deer species have a high lean meat:bone ratio (5.5:1 in FD and 5:1 in red deer) and a higher proportion of lean meat (from 66 to 83%) than more conventionally raised ruminant species (Kudrnáčová et al 2018 ). However, lower lean meat:bone ratio was noted (3.4:1) in this study although the results are in agreement with the findings of Kudrnáčová et al ( 2019 ), who reported a similar meat:bone ratio in 17-month old FD (3.42:1).…”
Section: Resultssupporting
confidence: 93%
“…However, the dressing percentage, in this study, was lower than reported by Stanisz et al ( 2015 ), Volpelli et al ( 2002 ) and Wiklund et al ( 2005 ) (55.5% vs. 63.3%, 57.7% and 67.2%, respectively), which was caused by a higher weight of internal organs and gastrointestinal tract in this study. In contrast, Kudrnáčová et al ( 2019 ) reported similar slaughter and carcass weights and dressing percentage (45 kg, 23 kg and 51%, respectively) for a 17-month-old farmed-raised FD from pasture feeding.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The effects of increasing dietary lysine levels on lipogenesis inhibition and the repartitioning of nutrients towards lean tissue deposition, instead of towards fat deposition, have been reported previously in monogastric farm animals, such as chickens [ 14 ], ducks [ 15 ] and pigs [ 16 ]. However, in previous work on FD, it was found that the supplementation of FD bucks with lysine also significantly decreased internal fat and carcass fat deposition [ 17 ]. Despite the fact that FD are one of the most popular deer species farmed world-wide, few studies have evaluated the effects of feeding concentrate and amino acid supplementations in this species.…”
Section: Introductionmentioning
confidence: 99%